KESIAPAN ANAK DAN PERAN ORANG TUA MUSLIM DALAM MEMPERSIAPKAN MENARCHE - Maharani, Nur; Widiasih, Restuning; Adistie, Fanny (Universitas Tribhuwana Tunggadewi, 2020)
Menarche a physiological process in puberty as a sign of the maturity in women’s reproductive organs. For Muslim women, a menarche is also an important event, because it signifies that a woman becomes 'baligh' (adult). Previous research shows that girls feel scared and unprepared when menarche, and limited information about family support for children. The purpose of this study was to examine the readiness of children and the roles of Muslim parents in dealing with menarche. This study applied a quantitative descriptive approach, the samples were selected using the purposive sampling technique, 176 students and parents from SDIT Imam Bukhari school involved in this study. The instrument was a questionnaire that assesses children's readiness and parents’ roles in assisting menarche. Data were analyzed using a frequency distribution.More than half of girls have good readiness (54.5%), and other children in the category moderate or poor. Parents as educators have a good role in preparing girls (52.3%) in component needs, motives, and goals. Most children are ready in dealing with menarche and getting support from parents. Providing menarche information at school would help children readiness especially who are in categories moderate and poor.